Non-destructive control of PVD coating surface defects - Romaniuk, S.P.; Bilinska, M.S.; Taran, A.V.; Klochko, O.Yu.; Nowakowska-Langier, K.; Marchenko, A.K.; Deryabkina, E.S.; Nikolaychuk, G.P. (Problems of Atomic Science and Technology, 2022)
Nanostructured ZrN coatings were deposited by the vacuum arc method with partial separation of the plasma flow from macroparticles using a curvilinear magnetic filter. With the proposed deposition parameters, a ZrN coating with an fcc lattice and (111) texture is formed. Theoretical studies are carried out to assess the defects of the surface layer in the presence of an adsorbed impurity of an fcc lattice with the surface orientation plane (111), and the characteristics of surface waves in the ZrN coating are considered. Equations are obtained for the dispersion laws and parameters of the splitting off of the surface wave from the zone of bulk vibrations in the nearest-neighbor approximation. Розглянуто параметри осадження наноструктурного покриття ZrN вакуумно-дуговим методом із частковою сепарацією плазмового потоку від макрочасток за допомогою криволінійного магнітного фільтра. При запропонованих параметрах нанесення формується покриття ZrN з ГЦК-ґратками та орієнтаційною площиною поверхні (111). Виконано теоретичні дослідження для оцінки дефектності поверхневого шару в вигляді адсорбованих домішок та розглянуто характеристики поверхневих хвиль у покритті ZrN. Отримано вирази для законів дисперсії та параметрів відщеплення поверхневої хвилі від зони об'ємних коливань при врахуванні найближчих сусідів.